(untitled) (Research, Society and Development, 2020)
Beet is a vegetable rich in antioxidant activity and phenolic compounds, besides being used as a natural dye, which has as a disadvantage the instability in relation to several factors, such as temperature, pH, oxygen and light. Therefore, this work aimed to microencapsulate the beet dye, evaluate the stability of powders and their application in yogurt. Beet extract was encapsulated in a combination of maltodextrin and xanthan gum, with subsequent drying in spray dryer or lyophilizer. In the powders obtained, color parameters, betanin content, phenolic compounds content, yield, microcapsule morphology and powder storage stability were evaluated for 40 days, with light, temperature and oxygen variation. The samples with the best results were applied in yogurt and the products were evaluated sensorially. The performance of powders dried by spray dryer was approximately 43% lower than lyophilized, with no variation in moisture content and soluble solids. Morphologically the samples dried by spray dryer were different from those dried by lyophilization. The content of phenolic compounds in the powders showed an increase after 40 days of storage in all samples, while the content of betanin showed a considerable drop in the first 7 days, followed by stability up to 40 days. With respect to color the parameter a*, was stable in storage, and the samples dried by spray dryer showed a higher value than the samples dried by lyophilization. The samples lyophilized with maltodextrin and with xanthan gum were added to the yoghurt, both in concentrations 0.5 and 1%. There was no significant difference between the yogurt samples prepared with the powders both in the sensory analysis and in the physical-chemical analysis, except for the ashes. Therefore, all the microcapsules evaluated presented good encapsulation efficiency and good stability during the 40 days evaluated.